Fostering Collaboration through Design Thinking: A Study among Software Engineering Students - Abich, Dariane; Parizi, Rafael; Marczak, Sabrina (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3544, 2024)
Design Thinking has been recognized for its potential to enhance critical thinking and collaboration skills, particularly in the initial stages of software development. However, despite its benefits, the effectiveness of Design Thinking can be reduced by insufficient engagement from professionals. Thus, it is crucial to foster an integrated practice environment that cultivates both technical competencies and interpersonal skills, such as collaboration, to better prepare students for the complexities of the field. This study investigates the role of Design Thinking in promoting collaborative skills among software engineering students through a case study involving 22 undergraduates engaged in a Design Thinking project over an 18-weeks long semester. Our analysis of interactions, project artifacts, and questionnaires using the 3C collaboration model (Communication, Coordination, Cooperation) pointed out that the iterative, user-centered process of Design Thinking fostered teamwork, idea sharing, and collaborative problem-solving. Our findings indicate that integrating Design Thinking into computing curricula could effectively prepare future software engineers with the dual competencies—technical and collaborative skills—required in professional life. Furthermore, the study offers practical recommendations for educators on implementing Design Thinking to enhance student collaboration. These insights also have broader implications for industry and researchers, providing a framework for applying Design Thinking principles to foster teamwork and problem-solving skills in professional and academic settings. Future studies should explore the long-term impacts of Design Thinking on students’ professional performance and investigate additional strategies to enhance coordination within collaborative projects.